Peptidylarginine Deiminases as Drug Targets in Neonatal Hypoxic–Ischemic Encephalopathy - Lange, Sigrun (Frontiers in Neurology, 2016)
Oxygen deprivation and infection are major causes of perinatal brain injury leading to cerebral palsy and other neurological disabilities. The identification of novel key factors mediating white and grey matter damage are crucial to allow better understanding of the specific contribution of different cell types to the injury processes and pathways for clinical intervention. Recent studies in the Rice-Vannucci mouse model of neonatal hypoxic ischaemia (HI) have highlighted novel roles for calcium-regulated peptidylarginine deiminases (PADs) and demonstrated neuro-protective effects of pharmacological PAD inhibition following HI and synergistic infection mimicked by LPS stimulation.